2016
DOI: 10.1099/jgv.0.000345
|View full text |Cite
|
Sign up to set email alerts
|

TLR2/MyD88/NF-κB signalling pathway regulates IL-8 production in porcine alveolar macrophages infected with porcine circovirus 2

Abstract: Porcine circovirus 2 (PCV2) is the primary cause of post-weaning multisystemic wasting syndrome, in which it stimulates a strong IL-8 response that is associated with chronic inflammation as well as lesions in the lymphoid organs. However, the mechanism underlying PCV2-induced IL-8 production is still unclear. In the present study, we demonstrated that increased IL-8 expression during PCV2 infection depends on Toll-like receptor (TLR2), but not TLR4 or TLR9 signalling pathways in porcine alveolar macrophages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…PCV2 can activate NF-κB signaling [25,28,31] and PCV2-induced IL-1β expression in PAMs is related to the activation of the NF-κB signaling pathway [32]. The phosphorylation of p65 during PCV2 infection was analyzed by Western blot based on phospho-specific antibody, p-p65.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCV2 can activate NF-κB signaling [25,28,31] and PCV2-induced IL-1β expression in PAMs is related to the activation of the NF-κB signaling pathway [32]. The phosphorylation of p65 during PCV2 infection was analyzed by Western blot based on phospho-specific antibody, p-p65.…”
Section: Resultsmentioning
confidence: 99%
“…BAY11-7082 (Selleckchem, USA), an inhibitor of NF-κB, by inhibiting the NF-κB p65 nuclear translocation and DNA binding activity, has been used in the research of NF-κB signaling pathway [25,27,28]. In this study, PAMs were pretreated with DMSO, BAY11-7082 (1 µM) for 1 h, as described previously [28], and infected with PCV2 at an MOI of 1. The cells and the supernatants were harvested after 12 h for analysis of IL-1β mRNA and protein by real-time RT-PCR and ELISA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to RIG-I-like signaling pathway, NF-κB signaling pathway also plays an important role in the production of inflammatory-related factors. Based on the previous results [9], we chose to test whether NF-κB signaling pathway was activated in PIECs following PCV2 infection. The qPCR results showed that the mRNA expression level of IκBα was significantly upregulated at 12 and 24 hpi in PCV2-PIECs group (P < 0.01) ( Fig.…”
Section: Pcv2 Does Not Activate Nf-κb Signaling Pathway In Piecsmentioning
confidence: 99%
“…Based on the previous results [9] and microarray results (unpublished data), we chose to investigate whether NF-κB and JNK signaling pathway were the key downstream pathway in this process. The results demonstrated that PCV2 infection could activate JNK but not NF-κB signaling pathway in PIECs.…”
Section: Jnk Signaling Pathway Contributes To the Upregulation Of Endmentioning
confidence: 99%
See 1 more Smart Citation